Socioeconomic Status in Relation to the Risk of Ovarian Cancer in African-American Women: A Population-Based Case-Control Study - Alberg, Anthony J. (Am J Epidemiol, 2016)
We investigated the association between socioeconomic status and ovarian cancer in African-American women. We used a population-based case-control study design that included case patients with incident ovarian cancer (n = 513) and age- and area-matched control participants (n = 721) from 10 states who were recruited into the African American Cancer Epidemiology Study from December 2010 through December 2014. Questionnaires were administered via telephone, and study participants responded to questions about several characteristics, including years of education, family annual income, and risk factors for ovarian cancer. After adjustment for established ovarian cancer risk factors, women with a college degree or more education had an odds ratio of 0.71 (95% confidence interval (CI): 0.51, 0.99) when compared with those with a high school diploma or less (P for trend = 0.02); women with family annual incomes of $75,000 or more had an odds ratio of 0.74 (95% CI: 0.47, 1.16) when compared with those with incomes less than $10,000 (P for trend = 0.055). When these variables were dichotomized, compared with women with a high school diploma or less, women with more education had an adjusted odds ratio of 0.72 (95% CI: 0.55, 0.93), and compared with women with an income less than $25,000, women with higher incomes had an adjusted odds ratio of 0.86 (95% CI: 0.66, 1.12). These findings suggest that ovarian cancer risk may be inversely associated with socioeconomic status among African-American women and highlight the need for additional evidence to more thoroughly characterize the association between socioeconomic status and ovarian cancer.